«Jubel og Kjærlighed, Fortvivlelse og Vanvid, Alt laa i dette tonende Væld» - Lise Karin Meling (Studia Musicologica Norvegica)
Abstract This article focuses on references to the piano in 19th-century Norwegian fiction. Using the Norwegian National Library’s digitized collections, I have located nearly 11.000 books published in the 19th century, and in these, I searched for the keywords “piano,” “pianoforte” and “klaver”. There are more than 1700 books containing at least one of these words: I then categorized the findings, according to the context or situations in which the words were applied in the literature. The findings testify to the diverse and fascinating role the piano played in the late 1800s: both as part of discourses concerning good breeding and as a means to get a marriage proposal, but also as a tool for expressing one's (unaccepted) emotions and sexuality. This article highlights perspectives on the social and gendered dimensions of music that are largely overlooked by other approaches, and thereby contributes to an increased understanding of gendered notions related to the piano.